Microencapsulamento de antocianinas de Jamelão (Syzygium cumini L.) - Paes, Francisco Elvino Rodrigues (2021)
Syzygium cumini L. is a fruit tree species native from India, belonging to the Myrtaceae family. The fruit of S. cumini L., the jamelão, has small proportions, an elliptical shape and an intense dark purple color. Intense is a characteristic of the presence of anthocyanins. Anthocyanins are natural water-soluble pigments found in nature in blue, purple and red color. These pigments are extremely related to changes in pH and elevated conditions. Microencapsulation is a technique applied to protect and increase the stability of materials of interest such as phenolic extracts from wild fruits. This technique is low cost and easy to apply on a large scale. In view of the properties of jamelon and the low applicability of this fruit, this work aims to produce an extract of anthocyanins extracted from jamelon and encapsulated by spray using β-clicodextrin (βCD) and maltodextrin (MA) in order to expand the Application of anthocyanins in the food industry. For this, the extract of anthocyanins from jamelón (EAJ) was produced, produced an emulsion with the wall material (βCD and MA) in the proportion of 1: 4 (v / v), EAJ: wall material, being possible in the end two : microcapsules synthesized with βCD (MβCD) and microcapsules synthesized with MA (MMA). Microcapsules were produced in a sprayryer. The synthesized microcapsules were evaluated for their physical characteristics using Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC) and Thermogravimetry (TGA). The characteristics were evaluated as Microencapsulation Efficiency (EM), Total Monomeric Anthocyanins (AMT), Infrared Absorption Spectroscopy (FT-IR), Total Extractable Polyphenols (PET), Total Antioxidant Activity (ATT) and Flavonoids. . For the EAJ, an analysis of antimicrobial activity against Staphylococcus aureus ATCC-27664, Escherichia coli ATCC-25922, Listeria monocytogenes ATCC-19115 and Salmonella enteritidis IAL-1132 was performed. Toxicological analysis was also performed against Artemia salina. For EAJ and MMA, bioaccessibility was evaluated. The results for the excellent SEM than as, MβCD and MMA, excellent microencapsulation dissipation with integral capsules, no cracks or extravasated nuclear material. A DSC analysis that indicates that as thermal resistance, the MβCD being more resistant than the MMA sample. The TGA reinforced the data found in the DSC where the degradation temperature for MβCD was around 300 ºC and for the MMA sample around 250 ºC. The data obtained in the EM sample showed that the MMA sample (93.01%) showed greater efficiency than the MβCD (40.42%). In the AMT analysis, values ​​of 47.04 mg.mL-1 were captured for the EAJ, 2.29 mg.mL-1 for MβCD and 27.3 mg.mL-1 for MA FT-IR indicated that the preg, MβCD and MMA, presence of carbohydrates, liquids, anthocyanins (peonidins, petunidins and malvidins). For PET, values ​​of 37.98 and 39.17 mg EAG/100g were found for MβCD and MMA, respectively. The ATT presented values ​​of 134.05 µM TEAC / g for the EAJ, 8.93 µM TEAC / g for an MβCD and 9.59 µM TEAC / g for an MMA. The EAJ has significant amounts of flavonoids, being found 185.92 mg / g. The EAJ also showed antimicrobial activity for the strains analyzed, with the exception of S. enteritidis. No values​​were found that indicate the toxicological effect for the extract or for the microcapsules against Artemia salina. According to the bioaccessibility analysis the MMA preservation preservation of 26.22% of the core material. Given the necessary data, it is possible to observe that AM was more efficient in containing anthocyanins, thus obtaining better results compared to PET and ATT.